Kinetic model of resonant nanoantennas in polymer for laser induced fusion - Papp, István; Bravina, Larissa; Csete, Mária; Kumari, Archana; Mishustin, Igor N.; Motornenko, Anton; Rácz, Péter; Satarov, Leonid M.; Stöcker, Horst; Strottman, Daniel D.; Szenes, András; Vass, Dávid; et al. (Frontiers in Physics, 2023)
Studies of resilience of light-resonant nanoantennas in vacuum are extended to consider the case of polymer embedding. This modifies the nanoantenna's lifetime and resonant laser pulse energy absorption. The effective resonance wavelength is shortened, the peak momentum of resonantly oscillating electrons in the nanorod is reduced by one-third, while the available lifespan of the resonance condition remains the same. This response is expected to strengthen the laser pulse induced nuclear fusion processes. Related numerical simulations were performed using particle-in-cell method in a simulation box of the size 0.223 $μ$m$^3$, treating the conduction electrons as strongly coupled plasma. In the modeling the polymer background was added with the experimentally measured refractive index of 1.53.